2021
DOI: 10.1111/spc3.12581
|View full text |Cite
|
Sign up to set email alerts
|

Taking charge and stepping in: Individuals who punish are rewarded with prestige and dominance

Abstract: A hallmark of human societies is the scale at which we cooperate with many others, even when they are not closely genetically related to us. One proposed mechanism that helps explain why we cooperate is punishment; cooperation may pay and proliferate if those who free ride on the cooperation of others are punished. Yet this ‘solution’ raises another puzzle of its own: Who will bear the costs of punishing? While the deterrence of free‐riders via punishment serves collective interests, presumably any single indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 127 publications
1
27
0
Order By: Relevance
“…Theoretical models suggest cooperative dynamics can emerge in conflict-prone groups in the context of inter-individual heterogeneity. For example, dominant leaders, or individuals who maintain influence via aggressive or coercive strategies (Mesterton-Gibbons and Dugatkin 1995;Cheng 2019), may more effectively enforce norms, levy punishments, and provide conflict resolution services than non or less dominant individuals (Mesterton-Gibbons et al 2011;Redhead, Dhaliwal, and Cheng 2021). Such services, however, also present opportunities for individual costs and collective action dilemmas.…”
Section: Leadership In Conflict Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical models suggest cooperative dynamics can emerge in conflict-prone groups in the context of inter-individual heterogeneity. For example, dominant leaders, or individuals who maintain influence via aggressive or coercive strategies (Mesterton-Gibbons and Dugatkin 1995;Cheng 2019), may more effectively enforce norms, levy punishments, and provide conflict resolution services than non or less dominant individuals (Mesterton-Gibbons et al 2011;Redhead, Dhaliwal, and Cheng 2021). Such services, however, also present opportunities for individual costs and collective action dilemmas.…”
Section: Leadership In Conflict Resolutionmentioning
confidence: 99%
“…However, Garfield, Syme, and Hagen (2020) (using the same data analysed here) found that providing punishment services was the strongest positive predictor of leaders with coercive authority, a quality strongly implicated in the dominance style of leadership (Cheng 2019) and punishment services by leaders was moderately associated with conflict resolution in results here. Although qualities linked to dominance-based influence may not be strongly or directly associated with resolving conflicts in the ethnographic record, there is potentially an indirect connection between abilities to enforce punishment and resolve conflict, with dominance-based influence (Redhead, Dhaliwal, and Cheng 2021).…”
Section: The Correlates Of Conflict Resolutionmentioning
confidence: 99%
“…The association of providing counsel and direction in followers affairs, rather than evidence for coercion, fear, manipulation or physical formidability, suggests conflict resolution often involves leaders advising followers and providing input influencing outcomes rather than mandating specific outcomes. The ethnographic evidence suggests across cultures, conflict resolution is less likely to be associated with coercive dominance-based influence and more likely to be associated with freely conferred prestige-based influence (Redhead, Dhaliwal, and Cheng 2021). Leaders who resolve conflicts are also likely to perform other prosocial group functions including, group representation, counselling and advising followers, and providing protection and punishment services.…”
Section: The Correlates Of Conflict Resolutionmentioning
confidence: 99%
“…Such individuals-commonly termed 'freeriders' or 'defectors'-may act selfishly and reap the benefits of a group's collective e↵orts without providing their own contributions [39,40]. Theory and evidence suggest that groups tackle free-riding, and reduce the costs of coordination, when certain individuals have disproportionate social influence (i.e., direct group e↵orts, and monitor the actions of others) [41][42][43], and when individuals who contribute to the collective e↵ort are rewarded [be those rewards social or material; 44,45].…”
Section: Macro-level Processes and The Emergence Of Social Hierarchiesmentioning
confidence: 99%